Impact of procalcitonin-guided therapy for hospitalized community-acquired pneumonia on reducing antibiotic consumption and costs in Japan. Issue 3 (March 2017) - Ito, Akihiro; Ishida, Tadashi; Tokumasu, Hironobu; Washio, Yasuyoshi; Yamazaki, Akio; Ito, Yuhei; Tachibana, Hiromasa
Abstract: Background and objective: This study aimed to investigate the usefulness of procalcitonin-guided therapy in hospitalized community-acquired pneumonia patients to reduce antibiotic duration and costs without worsening prognosis. Methods: 352 hospitalized community-acquired pneumonia patients in an observational cohort study in which procalcitonin was measured three times serially, on admission (Day 1) and 2–3 days (Day 3) and 6–8 days (Day 7) after admission, between October 2010 and February 2016 were reviewed retrospectively. Antibiotics could be stopped if Day 7 procalcitonin was <0.25 ng mL −1 or ≤10% of the higher value of procalcitonin on Day 1 or 3. Antibiotic duration and costs and recurrence and mortality rates were evaluated in mild to moderate or severe pneumonia by theoretical procalcitonin guidance for community-acquired pneumonia treatment. Results: Using theoretical procalcitonin guidance, antibiotic duration could be reduced from 12.6 to 8.6 days ( P < 0.001), while costs could be reduced from 45, 833 to 38, 952 yen ( P = 0.005). Among the patients in whom theoretical procalcitonin guidance could be adopted, recurrence rates (5.6% vs. 8.1%, P = 0.15) and mortality rates (0% vs. 5.1%, P = 0.07) did not worsen between the group having the same antibiotic durations as with theoretical procalcitonin guidance in actual practice (N = 71) and the group having durations more than 2 days longer in actual practice than in theoretical procalcitonin guidance (N = 198). There was no significant difference in pneumonia severity using A-DROP, CURB-65, and PSI between two groups. Conclusions: Procalcitonin-guided therapy may be useful in hospitalized community-acquired pneumonia patients to reduce antibiotic duration and costs without worsening the prognosis.